Essential issues in management accounting - Chartered Institute of Management Accountants (Hampshire : Workhouse Limited, 1993)
The video focuses on key management accounting techniques and how they have b een adopted in various business contexts; the four areas covered are standard costing, activity based costing, the theory of constraints and non-financial performance measurement
Keywords: Managerial accounting